EFESIENSI PRODUKSI USAHA TANI KAKAO ORGANIK STUDI KASUS KELOMPOK TANI SIDODADI DESA PUTAT KECAMATAN PATUK KABUPATEN GUNUNGKIDUL - Murniati, Murniati; Harli, Nurlina (Fakultas Pertanian, Universitas Janabadra, 2024)
Cocoa is an annual crop which is one of the leading commodities in the plantation sector, and is a source of livelihood for the community. The research objectives were to determine 1) production factors that influence organic cocoa production 2) production efficiency of organic cocoa farming in Putat Village, Patuk District. The research was conducted using a survey method using questionnaires on 30 cocoa farmers. The analysis model used is Cobb Douglas Linear Regression. The research results show that the land area factor has a significant effect on cocoa production, while fertilizer, plant age and labor have no significant effect on cocoa production. The efficiency of production factors is > 1, indicating that cocoa farming is not yet efficient.